Fetal endocrinology - Sunil Kumar Kota; Kotni Gayatri; Sruti Jammula; Lalit Kumar Meher; Siva Krishna Kota; S. V. S. Krishna; Kirtikumar D Modi (Indian Journal of Endocrinology and Metabolism, 2013)
Successful outcome of pregnancy depends upon genetic, cellular, and hormonal interactions, which lead to implantation, placentation, embryonic, and fetal development, parturition and fetal adaptation to extrauterine life. The fetal endocrine system commences development early in gestation and plays a modulating role on the various physiological organ systems and prepares the fetus for life after birth. Our current article provides an overview of the current knowledge of several aspects of this vast field of fetal endocrinology and the role of endocrine system on transition to extrauterine life. We also provide an insight into fetal endocrine adaptations pertinent to various clinically important situations like placental insufficiency and maternal malnutrition.